House of Risk (HOR): Analisis Risiko Aspek Waktu Pelaksanaan Bangunan Gedung di Lingkungan Lahan Basah Kalimantan Selatan - Candra Yuliana; Retna Hapsari Kartadipura; Endah Widiastuti; Gawit Hidayat (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2025)
Risks during project implementation are often related to lack of resources, design changes, which can result in work delays and increased costs. The aim of the research is to examine risks with a large impact in causing delays and effective ways to reduce them on construction projects in the Banjarbaru and Banjarmasin areas. This research involves data collection using qualitative method research through questionnaires, which are then analyzed using the Severity Index method combined with the Probability-Impact Matrix and House of Risk. The results of the identification of 5 dominant risks, namely quality checks at the same time as work implementation, staff organization, limited funds, inappropriate or uncomfortable PPE used during implementation, workers being too confident that they will not get hurt. Recommendations for dealing with project delays that can be achieved through setting appropriate specifications, evaluating the level of labor productivity and budget changes, checking quality according to standards, socializing the dangers of project accidents, monitoring in accident management, updating material and labor estimates, providing PPE.